A new role for cofilin in retinal neovascularization - Kumar, Raj (J Cell Sci, 2016)
Pak1 plays an important role in several cellular processes, including cell migration, but its role in pathological angiogenesis is not known. Here, we have determined its role in pathological retinal angiogenesis using an oxygen-induced retinopathy (OIR) model. VEGFA induced phosphorylation of Pak1 and its effector cofilin in a manner that was dependent on time as well as p38MAPKβ (also known as MAPK11) in human retinal microvascular endothelial cells (HRMVECs). Depletion of the levels of any of these molecules inhibited VEGFA-induced HRMVEC F-actin stress fiber formation, migration, proliferation, sprouting and tube formation. In accordance with these observations, hypoxia induced Pak1 and cofilin phosphorylation with p38MAPKβ being downstream to Pak1 and upstream to cofilin in mouse retina. Furthermore, Pak1 deficiency abolished hypoxia-induced p38MAPKβ and cofilin phosphorylation and abrogated retinal endothelial cell proliferation, tip cell formation and neovascularization. In addition, small interfering RNA (siRNA)-mediated downregulation of p38MAPKβ or cofilin levels in the wild-type mouse retina also diminished endothelial cell proliferation, tip cell formation and neovascularization. Taken together, these observations suggest that, although the p38MAPKβ–Pak1–cofilin axis is required for HRMVEC migration, proliferation, sprouting and tubulogenesis, Pak1–p38MAPKβ–cofilin signaling is also essential for hypoxia-induced mouse retinal endothelial cell proliferation, tip cell formation and neovascularization.